2021
DOI: 10.48550/arxiv.2111.13048
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neutrino Tomography of the Earth with ORCA Detector

F. Capozzi,
S. T. Petcov

Abstract: Using PREM as a reference model for the Earth density distribution we investigate in the present article the sensitivity of the ORCA detector to deviations of the Earth i) outer core (OC) density, ii) inner core (IC) density, iii) total core density, and iv) mantle density, from their respective PREM densities. The analysis is performed by studying the effects of the Earth matter on the oscillations of atmospheric ν µ , ν e , νµ and νe . We present results which, in particular, illustrate the dependence of the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The possibility of probing the internal structure of Earth using these density-dependent matter effects is known as "neutrino oscillation tomography". These studies have been performed using man-made neutrino beams [59][60][61][62][63][64][65][66][67][68][69], supernova neutrinos [70,71], solar neutrinos [70,[72][73][74][75][76][77], and atmospheric neutrinos [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92]. In the sub-GeV and multi-GeV energy ranges, atmospheric neutrinos are the best source of neutrinos to probe the internal structure of Earth because they have access to a wide range of baselines starting from about 15 km to 12750 km which cover all the layers of Earth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of probing the internal structure of Earth using these density-dependent matter effects is known as "neutrino oscillation tomography". These studies have been performed using man-made neutrino beams [59][60][61][62][63][64][65][66][67][68][69], supernova neutrinos [70,71], solar neutrinos [70,[72][73][74][75][76][77], and atmospheric neutrinos [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92]. In the sub-GeV and multi-GeV energy ranges, atmospheric neutrinos are the best source of neutrinos to probe the internal structure of Earth because they have access to a wide range of baselines starting from about 15 km to 12750 km which cover all the layers of Earth.…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity studies for current and future atmospheric neutrino experiments like IceCube [79], Oscillation Research with Cosmics in the Abyss (ORCA) [93], Deep Underground Neutrino Experiment (DUNE) [94], Hyper-Kamiokande (Hyper-K) [95], and Iron Calorimeter (ICAL) detector [85] have been performed. These studies have shown how to detect the presence of core-mantle boundary (CMB) using ICAL [85], constrain the average densities of the core, and the mantle using ORCA [80,87,88,92] and DUNE [86], determine the position of the core-mantle boundary using DUNE [89], and explore the chemical composition of the Earth core using Hyper-K and IceCube [79] as well as ORCA [81-83, 87, 91, 92].…”
Section: Introductionmentioning
confidence: 99%
“…The advancement in the precision of oscillation parameters with non-zero value of reactor mixing angle θ 13 has opened the door for Earth tomography based on matter effects on the oscillations of neutrinos in the multi-GeV energy range, which easily penetrate through the core. The possibility of such a "neutrino oscillation tomography" has been studied using man-made neutrino beams [36][37][38][39][40][41][42][43][44][45][46], solar neutrinos [47][48][49][50][51][52][53], supernova neutrinos [49,54], and atmospheric neutrinos [55][56][57][58][59][60][61][62][63][64][65][66]. During this propagation, neutrinos undergo charged-current interactions with ambient electrons and experience an effective Earth matter potential…”
mentioning
confidence: 99%
“…Since atmospheric neutrinos have energies in the multi-GeV range where the Earth matter effects are significant, and since about ∼ 20% of the upward-going atmospheric neutrinos observed at a detector would have passed through the core, this would be the best source of neutrinos to probe the core of the Earth. The use of atmospheric neutrinos for constraining the average densities of the core and the mantle using ORCA [57,63,66] and DUNE [64], for detecting the core-mantle boundary (CMB) using ICAL [62], and for determining the position of the core-mantle boundary using DUNE [65] has already been proposed. Note that the Earth matter effects on neutrinos depend on the electron density, as opposed to the matter density that the seismic waves are mainly sensitive to.…”
mentioning
confidence: 99%